The Kingdom of the Netherlands-Netherlands : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for The Kingdom of the Netherlands-Netherlands. (IMF Staff Country Reports; Country Report ;, 2019)
This Article IV Consultation highlights that the Dutch economy has grown faster than the euro area average over the past few years reflecting recovering consumption and investment, and strong net exports. Progress with tackling long-standing imbalances in the households and corporate sectors, and thus external imbalances, has lagged. Households remain highly leveraged and their consumption constrained by a stagnating disposable income. In the corporate sector, dominated by large multinational corporations, investment is low but savings are high, and developments are diverging with domestic small and medium enterprises relatively stagnant. Strong fiscal performance in recent years has boosted buffers that can now be used to reduce distortions and strengthen potential growth. The report recommends that it is important to harmonize tax benefits and social security contributions for different types of employment to reduce labor market duality while increasing overall labor market flexibility. Using fiscal space to address household and corporate imbalances is desirable and is unlikely to jeopardize long-term fiscal sustainability.